The Seduction of the Dialect in Visual Communication: Greek Cypriot Dialect in Print Advertisements - Papadima, Aspasia; Zantides, Evripides; Kourdis, Evangelos (My University, 2017)
Is it possible that a dialect can have a greater appeal than an official language? The answer appears to be positive, given that the dialect appears to be used more often as a semiotic tool in mass communication, and especially in advertising communication. Actually, although, in terms of communication, the study of language systems (standard languages, dialects, accents, etc.) falls under the sphere of sociolinguistics, these systems’ use in advertising messages suffice to highlight their semiotic dimension. Barthes (1964b: 101) considers advertising to be one of the systems of mass communication in which the senses are subject to an influx of images and graphic forms. But what happens when these visual signs and graphic signs are relegated to second place in communication when compared with the verbal message, as is the case with certain Greek‐Cypriot advertisements? In order to promote their advertised products, advertisers have made unexpected use of dialect in their advertising communication, setting aside the official language system, Modern Greek (MG) in favour of a variety of the Greek language, the Greek Cypriot Dialect (GCD), which is the consumers’ mother tongue. Kelly‐Holmes (2005: 109) believes that using the informal language system in advertising is meant to “create a feeling of community and to associate it with a particular product”. This choice is consistent with Magariños de Morentin’s (1987: 503) observation that the use of dialect in advertising messages constitutes “extra‐advertising semiosis”. It is this extra‐advertising semiosis that we plan to study in Greek Cypriot print advertisements published in the last two years, focussing our attention on the semiotic use of the verbal message and the typographic choices made with it in mind.
Semiotics and Visual Communication II: Culture of Seduction
Keywords: Greek Cypriot Dialect; Advertisements; Semiotic